Secondary water supply management for irrigation districts and canal companies - Wilkins-Wells, John, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2000)
One of the more important business practices over the years in larger multipurpose water districts has been the delivery of untreated water for lawns and gardens. This is generally in addition to traditional irrigation water deliveries. With rapid urbanization occurring in many rural agricultural counties, even smaller irrigation districts and canal companies are beginning to provide such service to small acreage subdivisions and a variety of other non-agricultural water users (golf courses, parks, etc.). It is a business innovation stemming from urbanization in traditional and, for the most part, prime irrigated lands throughout the West. This paper presents two case studies of untreated water delivery for lawns and gardens by such enterprises. It discusses some of the issues surrounding the development of this practice, the costs and benefits of engaging in this kind of water service, and what opportunities and constraints lay ahead for this business practice in the future.
Irrigation and drainage in the new millennium
Not digitized by CSUL Digital Services.
Presented at the 2000 USCID international conference, Challenges facing irrigation and drainage in the new millennium on June 20-24 in Fort Collins, Colorado.